2021
DOI: 10.1108/tqm-08-2020-0183
|View full text |Cite
|
Sign up to set email alerts
|

The impact of quality management practices on knowledge management processes: a study of a social security corporation in Jordan

Abstract: PurposeThis study aimed to investigate the impact of total quality practices on knowledge management (KM) processes across a Social Security Corporation (SSC) in Jordan and explore the best approach to improve KM processes using quality management.Design/methodology/approachThis study followed a quantitative methodology: a conceptual model was developed based on an extensive review of the related literature; an online survey was developed and distributed using the SSC's intranet; and 384 surveys were completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 70 publications
2
18
0
Order By: Relevance
“…Poor airline service quality causes passenger dissatisfaction, according to Hu and Hsiao (2016). Customers' perceptions have a significant impact on service sectors since they serve as quality inspectors (Al Shraah et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Poor airline service quality causes passenger dissatisfaction, according to Hu and Hsiao (2016). Customers' perceptions have a significant impact on service sectors since they serve as quality inspectors (Al Shraah et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much has been written on the importance of managing knowledge processes, that is, about the processes that are used to identify, capture, share and use project-based knowledge, but considerably less has been written on the exact mechanisms for managing this process in MoOSTs [24,35,37]. A review of the literature has identified different elements of KMP, but they can all be distinguished under four key KMP elements, namely, knowledge creation (KC), knowledge transfer (KT), knowledge storage/retrieval (KSR) and knowledge application (KA) [38][39][40]. KC refers to accumulation of knowledge, in project-based organisations such as MoOSTs, knowledge identification (KI) and KC do not have clear boundaries separating them, and mostly have similar connotations [41].…”
Section: Knowledge Management Process (Kmp) In Moostsmentioning
confidence: 99%
“…This is explained by the fact that this direction is connected both ideologically and instrumentally with quality management, ISO standards, for which relevant studies of both theoretical and practical nature have been conducted for quite some time. Examples of such studies can be [2][3][4], in which at tention is paid to those procedures and tools from quality management that are used in project management, taking into account the recommendations of the standards. At the same time, special attention is paid to business processes as the basis for managing the quality of the project pro duct (for example, [5][6][7]).…”
Section: Introductionmentioning
confidence: 99%